Effect of Hypovitaminosis D on Postoperative Pain Outcomes and Short-Term Health-Related Quality of Life After Knee Arthroplasty: A Cohort Study. Issue 42 (October 2015) - Lee, Anna; Chan, Simon Kin Cheong; Samy, Winnie; Chiu, Chun Hung; Gin, Tony
Abstract : Abstract: Vitamin D may have an important role in pain perception. Inadequate vitamin D levels are associated with suboptimal recovery after surgery. However, the effects of hypovitaminosis D on postoperative pain-related outcomes and its impact on health-related quality of life after surgery are not well understood. The objective of this study was to determine the effects of hypovitaminosis D on postoperative pain-related outcomes and health-related quality of life at 3 months after knee arthroplasty. This was a longitudinal cohort study of 191 consecutive Hong Kong Chinese patients who were given patient-controlled morphine analgesia for up to 72 hours after 214 knee arthroplasties. Serum total 25-hydroxyvitamin D (25-OHD) concentration was assessed by liquid chromatography-tandem mass spectrometry. The primary outcomes were postoperative pain intensity at rest scores (0–72 h), Western Ontario and McMaster Universities (WOMAC) osteoarthritis index (pain, stiffness and function), and moderate-to-severe persistent pain (transformed WOMAC pain score of 0–75 at 3 months after knee arthroplasty; 0, extreme pain; 100, no pain). Group differences were analyzed using generalized estimating equation models and a logistic regression model. The prevalence of preoperative hypovitaminosis D (25-OHD <50 nmol/L) was 44% (95% confidence interval [CI]: 37%–51%). There were transient higher pain intensity scores in the moderate-to-severe hypovitaminosis D (25-OHD <30 nmol/L) group compared with the sufficient vitamin D group. Vitamin D status had no effect on total WOMAC index ( P = 0.22). The incidence of moderate-to-severe persistent pain was 9% (95% CI: 6%–14%). Hypovitaminosis D increased the risk of moderate-to-severe persistent pain (adjusted odds ratio 2.64, 95% CI: 1.03–6.77). Preoperative hypovitaminosis D had subtle effects on pain intensity scores in the early postoperative period and is a risk factor for moderate-to-severe persistent pain after knee arthroplasty. Hypovitaminosis D was not associated with worse health-related quality of life at 3 months after knee arthroplasty.